Selective clustering scheme based on user equipment path and frequency reuse scheme for coordinated multi‐point joint processing. Issue 17 (1st November 2014) - Chung, Sungmoon; Jang, Seokmin; Joe, Inwhee
Abstract : Coordinated multi‐point (CoMP) – joint processing (JP) is a technique which improves the cell edge user data rate and spectral efficiency. The practical requirements for CoMP‐JP in terms of capacity and latency constraints should be solved by considering backhaul network. The possibility of deploying CoMP‐JP in practical cellular systems strongly depends on the backhaul network capabilities. The authors propose a selective clustering scheme which is able to selectively form clusters in order to decrease the traffic load of the backhaul network for CoMP‐JP. In addition, the authors propose a new frequency reuse scheme for downlink CoMP‐JP. The authors are able to decrease intra‐cell and inter‐cell interference with our proposed frequency reuse scheme. Therefore the authors increase the spectral efficiency and SINR (signal to interference and noise ratio) performance of the system.